Text Messaging Intervention for Teens and Young Adults With Diabetes. (September 2014) - Markowitz, Jessica T.; Cousineau, Tara; Franko, Debra L.; Schultz, Alan T.; Trant, Meredith; Rodgers, Rachel; Laffel, Lori M. B.
Adolescents and young adults use text messaging as their primary mode of communication, thus providing an opportunity to use this mode of communication for mobile health (mHealth) interventions. Youth with diabetes are an important group for these mHealth initiatives, as diabetes management requires an enormous amount of daily effort and this population has difficulty achieving optimal diabetes management. Goal setting and self-efficacy are 2 factors in the management of diabetes. We examined the feasibility of a healthy lifestyle text messaging program targeting self-efficacy and goal setting among adolescents and young adults with diabetes. Participants, ages 16-21, were assigned to either a text messaging group, which received daily motivational messages about nutrition and physical activity, or a control group, which received paper-based information about healthy lifestyle. Both groups set goals for nutrition and physical activity and completed a measure of self-efficacy. Participants' mean age was 18.7 ± 1.6 years old, with diabetes duration of 10.0 ± 4.6 years, and A1c of 8.7 ± 1.7%. The text messaging intervention was rated highly and proved to be acceptable to participants. Self-efficacy, glycemic control, and body mass index did not change over the course of the short, 1-month pilot study. Positive, daily, motivational text messages may be effective in increasing motivation for small goal changes in the areas of nutrition and physical activity. These interventions may be used in the future in youth with diabetes to improve diabetes care. Utilizing more targeted text messages is an area for future research.